2013
DOI: 10.32385/rpmgf.v29i6.11197
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência e impacto da incontinência urinária na qualidade de vida da mulher

Abstract: INTRODUÇÃOA definição de incontinência urinária (IU) como qualquer perda involuntária de urina (no último ano ou mês) foi introduzida pela Internacional Continence Society, com o intuito de uniformizar os estudos epidemiológicos, atendendo a que até então o conceito de IU era variável e dependente das diferentes culturas, países, estilos de vida, género e idade. 1,2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 39 publications
0
5
0
2
Order By: Relevance
“…The findings on the general prevalence of UI corroborate the results of population-based studies conducted with elderly people in São Paulo (São Paulo) 6 and in Florianópolis (Santa Catarina) 8 . However, research on the prevalence of UI has shown great variability 7,11,12,17,19,21,33 . This may occur due to sample choice, the age and gender of the population investigated 33 , the fact that prevalence is often higher among elderly persons in long-term institutions 19 ; and the type of instrument used for UI assessment, whether self-reported or clinical diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings on the general prevalence of UI corroborate the results of population-based studies conducted with elderly people in São Paulo (São Paulo) 6 and in Florianópolis (Santa Catarina) 8 . However, research on the prevalence of UI has shown great variability 7,11,12,17,19,21,33 . This may occur due to sample choice, the age and gender of the population investigated 33 , the fact that prevalence is often higher among elderly persons in long-term institutions 19 ; and the type of instrument used for UI assessment, whether self-reported or clinical diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, research on the prevalence of UI has shown great variability 7,11,12,17,19,21,33 . This may occur due to sample choice, the age and gender of the population investigated 33 , the fact that prevalence is often higher among elderly persons in long-term institutions 19 ; and the type of instrument used for UI assessment, whether self-reported or clinical diagnosis. This variability can also be explained by the adoption of different definitions for UI or even different methodologies 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Adherence rate is influenced by negative aspects such as the need for preserved cognition, the presence of pain, the possibility of urethral injury. For this reason, CIC could impact daily life activities in some patients . To solve these problems, the present study aimed to evaluate the performance of a new intraurethral self‐retaining device (ISRD) in the female with neurogenic bladder, as a possible alternative to CIC.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, CIC could impact daily life activities in some patients. 8,9 To solve these problems, the present study aimed to evaluate the performance of a new intraurethral self-retaining device (ISRD) in the female with neurogenic bladder, as a possible alternative to CIC.…”
Section: Introductionmentioning
confidence: 99%
“…No Brasil, a realização de estudos de prevalência de IUE é precária, mas considera--se alta a prevalência na população feminina, variando de 5-69%, geralmente em função da idade, do nível cultural, da gravidade da disfunção e da baixa notificação. Desta forma, o impacto da incontinência sobre a vida diária dessas mulheres acarreta danos consideráveis, mas em nível nacional não existem muitas pesquisas indexadas relatando o efeito desses danos 3,4 .…”
unclassified